Optimal Power Distribution Strategy for Intermittent Solar-Powered Hybrid Energy Storage Systems: Strategi Distribusi Daya yang Optimal untuk Sistem Penyimpanan Energi Hibrida Bertenaga Surya yang Bersifat Intermiten - Indah Sulistiyowati; Jamaaluddin Jamaaluddin; Izza Anshory; Yunardhika Wahyu Pratama; Sahrul Romadhoni (Universitas Muhammadiyah Sidoarjo, 2023)
Addressing challenges in solar panel systems, hybrid energy storage systems have gained prominence but face distribution imbalances. This study presents a power distribution approach for hybrid systems in intermittent solar scenarios, leveraging First-Order Filters to allocate power between primary and supporting storage. By employing Lowpass and Highpass First-Order Filters, energy management issues in off-grid systems are addressed. Experimental findings reveal that during high intermittency, the battery stores 387 W and contributes 62 W, while the supercapacitor stores 297 W and contributes 167 W as the primary storage. Conversely, during low intermittency, the battery stores 390 W and contributes 62 W, while the supercapacitor stores 295 W and contributes 164 W. Surprisingly, the supercapacitor doesn't outperform the battery in power efficiency as the primary storage. This work contributes to enhancing the viability of solar-powered hybrid energy storage systems by optimizing power distribution strategies. Highlight: Distribution Imbalances in Hybrid Systems: Hybrid energy storage systems for solar panels face challenges in power distribution, motivating the need for innovative solutions. First-Order Filter Allocation: This research introduces a power distribution approach utilizing First-Order Filters to effectively allocate power between primary and supporting storage in intermittent solar scenarios. Comparative Power Efficiency: Experimental results demonstrate the performance of battery and supercapacitor as primary storage, revealing unexpected power efficiency outcomes under varying solar intermittency, informing strategic energy management decisions. Keywrod: Hybrid Energy Storage, Power Distribution, Intermittent Solar Scenarios, First-Order Filters, Energy Management